2021
DOI: 10.22430/22565337.1822
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de los parámetros de operación de la extracción asistida por ultrasonido en la obtención de polifenoles de uva: una revisión

Abstract: Los compuestos fenólicos han sido de gran relevancia para su aplicación en industrias como la farmacéutica y la alimentaria. Esto ha llevado al estudio de métodos de extracción eficientes en cuanto a rendimiento, capacidad antioxidante y costos de operación. La extracción asistida por ultrasonido ha reportado resultados superiores en comparación con los métodos de extracción convencionales, además de ser amigable con el medio ambiente. En este sentido, este artículo tiene como objetivo evaluar el efecto de los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
(26 reference statements)
0
3
1
Order By: Relevance
“…This difference may be explained by the traditional extraction method used in said study because it is known that yields are higher when ultrasound-assisted extraction is implemented [ 71 ]. Ramón and Gil-Garzón reported a TCP 93% lower than that obtained here, which explains the lower antioxidant capacity they found [ 40 ]. These results prove the importance of time optimization, sample extenuation, and entire matrix evaluation.…”
Section: Resultscontrasting
confidence: 65%
See 1 more Smart Citation
“…This difference may be explained by the traditional extraction method used in said study because it is known that yields are higher when ultrasound-assisted extraction is implemented [ 71 ]. Ramón and Gil-Garzón reported a TCP 93% lower than that obtained here, which explains the lower antioxidant capacity they found [ 40 ]. These results prove the importance of time optimization, sample extenuation, and entire matrix evaluation.…”
Section: Resultscontrasting
confidence: 65%
“…A literature review that examined publications in this field between 2013 and 2022 [ 40 ] did not find any previous studies reporting the bromatological analysis of the V. labrusca grape variety. Therefore, Thus, in this study, it was determined that the fiber and ash content of Isabella grapes grown under organic agronomic practices 51.1% and 35.2%, respectively) was higher than the values reported by Bender et al (2020) [ 41 ] , who found a fiber percentage of 4.06% ± 1.31 and an ash percentage of 5.14% ± 0.00 in Vitis vinifera L dry weight.…”
Section: Resultsmentioning
confidence: 99%
“…31 µg Trolox/g ms) with natural antioxidants, presented higher antioxidant activity than the formulations with the commercial antioxidant BHT 7 (CP + SIOPH + BHT (200 ppm) + GA) (4641.18 ± 11.18 µg Trolox/g ms) and 8 (CP + SIOPH + BHT (200 ppm) + GA + MD) (3428.41 ± 11.06 µg Trolox/g ms). These results are due to the high content of phenolic compounds in the aji charapita pepper and grape orujo [ 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…It generates acoustic cavitation in the liquid medium randomly and constantly, releasing a large amount of energy through turbulence and mass transfer. It collapses the bubbles violently and with pressure against the propolis to favor the interaction with the solvent [30,31]. This study aimed to evaluate the inhibitory potential of A-amylase and A-glucosidase enzymes of bioactive compounds extracted with ultrasound from propolis under simulated digestion conditions.…”
Section: Introductionmentioning
confidence: 99%